The cooperative on-street parking space searching mechanism in city environments. (March 2019) - Horng, Gwo-Jiun
Abstract: In this paper, we aim to design an innovative parking space searching space occupancy indicator (SOI) system. Searching for a parking space is a common global problem that needs urgent solutions. The proposed mechanism uses taxis, public vehicles (PVs), and on-street parked vehicles to sense parking spaces and transmits sensed information to nearby road side unit (RSU) hotspots. The transmitted data include the availability of parking spaces and their location and direction. We use a cellular automata (CA) model and small world mechanism to achieve on-street parking space searching and recommendation. The current study evaluates the performance of the approach by conducting computer simulations. Simulation results reveal the strengths of the proposed optimized and parking space searching SOI system in terms of reduces search time, and increases success rate of tracking in VANETs.